From ‘Adeola’ to ‘HarDeyOlar’: Unpacking the Effects of Self-Naming Trends on Identity and Language in GenZee Subcultures - ADEDOTUN, Toyin Florence; AJEPE, Ife; ADEMOWO, Adeyemi Johnson (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This study explores the self-naming phenomenon among GenZee students in selected tertiary institutions in Ekiti State, Nigeria, focusing on the alteration of traditional Yoruba names (e.g., “Adeola” to “HarDeyOlar”) as a form of cultural expression and self-identity reconfiguration. Rooted in both postcolonial and sociolinguistic frameworks, the work examines how GenZees’ engagement with self-naming reflects deeper issues of indigenous language use, identity transformation and the dynamics of modernity in postcolonial African societies. The study is situated within discussive paradigms regarding the impact of globalisation on local cultures, especially indigenous naming practices which signified traditional or cultural heritage, family history and social status within the Yoruba culture. Data were collected through semi-structured interviews and focus group discussions with 60 purposively selected GenZee students from two universities and polytechnics (private and public) in Ekiti State, to capture the personal motivations behind name alterations. Using thematic analysis, the data were analysed to identify recurring themes such as perceived modernity, global identity aspirations, and the perceived obsolescence of indigenous linguistic forms. Findings reveal that self-naming serves as both an assertion of individual agency and a response to societal pressures favouring westernised or hybrid identities, potentially accelerating the erosion of indigenous language usage among youths. This study contributes to the discourse on cultural retention versus adaptation in African societies, highlighting self-naming as a significant factor in the negotiation between tradition and modernity. The implications of these trends underscore broader challenges in cultural preservation, language sustainability, and identity politics in Nigeria and similar postcolonial contexts.